Transplanting in redgram for resource effective crop production to unleash the potential yield - N M, Sunilkumar; Kamthane, Jyothi; Mallikarjun, Ningadalli; Bulla, Gnyandev; Goudappa, S B; Rayudu, B T; Venkatasubramanian, V (Indian Farming, 2024)
In India, redgram or pigeonpea (Cajanus cajan) is predominantly cultivated in Uttar Pradesh, Madhya Pradesh, West Bengal, Bihar, Jharkhand, Maharashtra, Karnataka, Andhra Pradesh, Telangana, Gujarat, Odisha, Chattisgarh, and Tamil Nadu. It is one of the major pulse crops in Northern Karnataka, covering approximately 5.14 lakh ha with a production of 2.42 lakh tonnes (766 kg/ha). Bidar district, known as the pulse bowl of Karnataka, accounts for a significant share of redgram cultivation, spanning 65,642 ha. However, dry land cultivation of redgram faces various agronomic challenges and inefficient water management, leading to diminishing productivity amidst water scarcity and rainfall uncertainty. Addressing these challenges, ICAR-KVK, Bidar initiated a trial on redgram transplanting after collaborative discussions with progressive farmers and scientists in 2004-05, yielding promising results. Subsequently, ICAR-KVK, Bidar conducted various activities like on-farm trials (OFTs), frontline demonstrations (FLDs), capacity-building programs, and farm advisory services. Through FLDs, redgram transplanting technology was standardized, achieving an average seed yield of 29.70 quintals/ha and net income of ₹ 1,07,240/ha compared to traditional practices, with an average yield of 17.5 quintals/ha and net income of ₹ 58,500/ha during 2009-10 to 2014-15. Adoption of transplanting technology resulted in yield increases ranging from 69.71% to 138% compared to traditional practices. ICAR-KVK, Bidar standardized redgram transplanting technology by preparing healthy seedlings of 30-day-old and transplanting them in the field. This technology adoption led to unprecedented yields, prompting its horizontal spread to 2000 hectares in Bidar district and neighbouring districts of Karnataka, Maharashtra, Telangana, Andhra Pradesh, Odisha, Chattisgarh, and Tamil Nadu. Redgram transplanting offers several advantages including higher yields and income, and has become a resource-efficient crop production approach tailored to the specific needs of small and marginal farmers in dry land farming areas, not only in Bidar district but also across Karnataka and other states nationwide.